Ethnoscience-Based Module: Biodiversity Materials in Lembak Tribe - Walid, Ahmad; Winarni, Endang Widi; Yanti, Fitri April; Firdaus, M. Lutfi; Suherman, Suherman; Zulkarnain, Zulkarnain (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Efforts to conserve plants and documentation of related local knowledge in the Dendam Tak Sudah Lake, Dusun Besar Village, Bengkulu City area are important to carry out and introduce to students. The study aims to synthesize the biodiversity material modules developed to identify the types of medicinal plants found in Dusun Besar Village. Thiagarajan's development model section is define, design, develop, and disseminate. Identification, synthesis, feasibility, response, and analysis data were obtained as research data. The module was piloted in five elementary schools in Bengkulu City. The study found 20 types of medicinal plants, including the most commonly used hereditary species in the Lembak community. The validation results show that the criteria are very valid, with an expert validator value of 85%. The module also received an excellent response rate of 82%. Therefore, the biodiversity material modules are very attractive, feasible, and effective for learning biodiversity materials in elementary schools.